EFFECTIVENESS OF CHATBOT TO REDUCE THE RISK OF CORONARY HEART DISEASE WITH DOKTERKIT MOBILE APPLICATION - Agnes Atmadjaja; Minarni Watiningsih; Stefani Nurhadi (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: An innovative approach in the form of a discussion platform designed to help users deal with health issues related to coronary artery disease. Chatbot platforms allow the collection of users' data, which is analyzed through natural language processing and behavioral analysis to provide each user with a customized solution based on their current situation. The data collected and analyzed is accessible. The platform is developed using chatbot technology. Users can interact with chatbots to generate personal chat data stored on the platform.Conflicting information and sensitivity to Coronary heart disease (CHD) issues hinder effective communication. Recent technological solutions to maintain weight loss are limited. A chatbot would be suitable to support weight loss as it requires no human intervention, is available 24 hours a day, and supports natural communication while maintaining anonymity. CHD is a non-communicable disease with increased mortality in both developed and developing countries. It is a major public health problem worldwide. There are many risk factors for coronary heart disease, divided into primary risk factors (age, gender, genetics) and secondary risk factors (hypertension, smoking, dyslipidemia, diabetes, obesity, physical inactivity), and other risk factors (stress, alcohol, diet, and nutrition).The health system needs an effective and low-cost way to provide optimal health outcomes. Conversational Artificial Intelligence (AI) capabilities in the form of a fully automated and self-contained text-based mobile tutoring service. CHD is a serious health problem worldwide with multiple and interrelated causes. At the same time, chatbots are becoming more popular for interacting with users in mobile health apps.Objective: Dokterkit mobile application (available on the Google Play Store) prevents lifestyle-related diseases that are a risk for CHD, which has been considered to be at risk for multiple coronary artery disease (CAD), with the overarching goal of gaining compassion through mobile health improvements Opportunities for the healthcare of the heart. The insights gained in this preview article are used to plan future healthcare systems and design a system embedded with artificial intelligence to advance healthcare, chronic disease prevention, and self-treatment.Results: The Role of Artificial Intelligence in preventing Coronary Heart Disease (CHD) is to routinely carry out health screenings, make users aware of exercising regularly, and maintain food intake by reducing foods that are high in calories and adding foods that are high in fiber.Conclusion: Using AI in healthcare is associated with preventing CHD, which alters healthy lifestyles. It can also encourage a change in attitude, a high level of user concern for health, and obtain complete health information. Research on artificial intelligence and its use in telemedicine needs to be continued, with clinical trials examining the impact on blood pressure, body mass index, smoking, diabetes mellitus, and user engagement and feedback.